Impact of social factors and health campaigns on the burden of idiopathic epilepsy: an inequality, decomposition, generalized and synthetic difference-in-differences study - Xuewen Rong; Dongting Yu; Wei Zhao; Jingyu Xiao; Du Feng; Gengfeng Chen; Zemeng Cao; Liming Shu (Frontiers in Public Health)
BackgroundIdiopathic epilepsy is a major global health burden that causes premature death and disability. Previous studies have systematically analyzed trends in the burden of idiopathic epilepsy. However, analyses of the impact of social factors, health campaigns and policies on the burden of idiopathic epilepsy are lacking. This study aims to fill that gap.MethodsWe used data from the 2021 Global Burden of Disease (GBD) and calculated the estimated annual percentage changes (EAPC) to assess trends. Decomposition analysis breaks down changes in the burden of idiopathic epilepsy into three factors. Correlation analysis measures the association between the EAPC and social development. Inequality analysis illustrates the disparity in the burden of idiopathic epilepsy among countries. Generalized difference-in-differences (GDID) and synthetic difference-in-differences (SDID) analyses are used to quantify the impact of health campaigns or policies on the burden of idiopathic epilepsy.ResultsWith respect to incidence, aging had a negative impact. The correlation between the sociodemographic index (SDI) and EAPC had a rho value of −0.18. The slope index of inequality for the mortality burden decreased from 1.97 to 1.62. After the policy shock, the age-standardized rate (ASR) of years lived with disability (YLD) in the Caribbean increased significantly to 4.59 (95% CI: 0.96 to 8.22), while the all-age YLD rate in the U.S. increased (5.18, 95% CI: 0.66 to 9.70) for both sexes.ConclusionThis study explores the impact of social factors and health campaigns on the burden of idiopathic epilepsy. We emphasize the need for targeted prevention and treatment strategies to effectively address the burden of idiopathic epilepsy.